Pregnant Women's Knowledge and Attitudes Towards Antenatal Care (ANC) Services at Siko Public Health Center - Eka Lestari Duwila; Sulistiyah Sulistiyah; Reny Retnaningsih (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
Antenatal care (ANC) is critical for ensuring the health and well-being of pregnant women and their fetuses, particularly in reducing maternal mortality rates, which remain high in Indonesia. One of the contributing factors to this issue is a lack of knowledge and non-compliance with ANC visits. The goal of this study is to examine the knowledge and attitudes of pregnant women towards ANC services at Puskesmas Siko, a health center located in Indonesia. The study used a descriptive quantitative approach with a cross-sectional design. A sample of 34 pregnant women was selected using purposive sampling. A structured questionnaire was administered to assess their knowledge and attitudes regarding ANC services. Data analysis was conducted using the Chi-Square test. The results indicated a significant relationship between pregnant women’s knowledge and their adherence to ANC visits, with a p-value of 0.001 (p < 0.05). Similarly, the study found a significant relationship between the attitudes of pregnant women and their participation in ANC visits, with a p-value of 0.004 (p < 0.05). These findings suggest that pregnant women who possess more knowledge and have a positive attitude toward ANC are more likely to utilize these services. The study highlights the critical role that improving knowledge and attitudes plays in increasing ANC utilization, which is essential for preventing pregnancy-related complications and improving overall maternal health outcomes. Given the significant impact of ANC on reducing maternal and fetal health risks, it is crucial to implement targeted health education programs that aim to enhance pregnant women’s understanding of ANC’s importance and encourage positive attitudes towards attending these visits. The findings from this study call for greater emphasis on health education interventions that can improve the knowledge and attitudes of pregnant women, thereby contributing to a reduction in maternal mortality and improved pregnancy outcomes in the region.